(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article examines Mark Twain's Life on the Mississippi, highlighting its narrative style, historical context, and cultural significance. It explores Twain's insights into the life of riverboat pilots and the evolution of the Mississippi River ecosystem, providing an essential reflection on American society in the 19th century